The unique and compensatory effects of home and classroom learning activities on Migrant and Seasonal Head Start children’s Spanish and English emergent literacy skills - Luo, Rufan; Song, Lulu (Frontiers in Psychology, 2022)
Children of migrant and seasonal farmworkers (MSFW) are among the most underprivileged, underserved groups in the United States. The current study examined how home and classroom language and literacy experiences uniquely and interactively contributed to MSFW children’s emergent literacy skills in English and Spanish. Participants were 255 Spanish-English dual language learning children (Mage = 49 mon; 98.3% Latino/Hispanic) and their parents and 47 teachers, drawn from the Migrant and Seasonal Head Start (MSHS) Study. Parents reported how often the target children engaged in language and literacy activities (i.e., teaching letters, words, or numbers, book-reading, singing, and storytelling) with their family members. Teachers reported how often the target children engaged in classroom language and literacy activities (e.g., book-reading, learning letters, retelling stories, etc.). Children’s emergent literacy skills in English and Spanish were assessed by standard tests. After controlling for demographic variables, home and classroom language and literacy activities uniquely predicted children’s emergent literacy skills in Spanish, but not in English. Additionally, home and classroom activities compensated one another in supporting children’s English and Spanish emergent literacy development. That is, language and literacy activities in one context showed a stronger effect for children who experienced less frequent activities in the other context. Together, these findings shed light on ways to support MSFW children’s emergent literacy skills and reveal the importance of integrating and connecting home and school learning experiences.